An exploratory study to evaluate whether medical nutrition therapy can improve dietary intake in hospital patients who eat poorly. Issue 6 (23rd October 2013) - Agarwal, E.; Ferguson, M.; Banks, M.; Bauer, J.; Capra, S.; Isenring, E.
Abstract Background The Australasian Nutrition Care Day Survey (ANCDS) reported that two‐fifths of patients consume ≤50% of the offered food in Australian and New Zealand hospitals. After controlling for confounders (nutritional status, age, disease type and severity), the ANCDS also established an independent association between poor food intake and increased in‐hospital mortality. The present study aimed to evaluate whether medical nutrition therapy (MNT) could improve dietary intake in hospital patients eating poorly. Methods An exploratory pilot study was conducted in the respiratory, neurology and orthopaedic wards of an Australian hospital. At baseline, percentage food intake (0%, 25%, 50%, 75% and 100%) was evaluated for each main meal and snack for a 24‐h period in patients hospitalised for ≥2 days and not under dietetic review. Patients consuming ≤50% of offered meals as a result of nutrition‐impact symptoms were referred to ward dietitians for MNT. Food intake was re‐evaluated on the seventh day after recruitment (post‐MNT). Results One hundred and eighty‐four patients were observed over 4 weeks; 32 patients were referred for MNT. Although baseline and post‐MNT data for 20 participants [mean (SD) age 68 (17) years, 65% females] indicated a significant increase in median energy and protein intake post‐MNT (3600 kJ day−1; 40 g day−1) versus baseline (2250 kJ day−1; 25 g day−1) (P < 0.05), the increased intake met only 50% of dietary requirements. Persistent nutrition impact symptoms affected intake. Conclusions In the present pilot study, although dietary intake improved, it remained inadequate to meet participants' estimated requirements as a result of ongoing nutrition‐impact symptoms. Appropriate medical management and early enteral feeding could be a possible solution for such patients.